2013
DOI: 10.15802/stp2013/14202
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and methodological bases of psychological and psychophysical training of students in the process of physical education

Abstract: Наука та прогрес транспорту. Вісник Дніпропетровського національного університету залізничного транспорту, 2013, вип. ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ОСНОВИ ПСИХОЛОГІЧНОЇ І ПСИХОФІЗИЧНОЇ ПІДГОТОВКИ СТУДЕНТІВ У ПРОЦЕСІ ФІЗИЧНОГО ВИХОВАННЯМета. Виявити теоретико-методологічні основи для проведення психологічної і психофізичної підготов-ки студентів в процесі фізичного виховання. Методика. В якості методу дослідження використано теоре-тичний аналіз. Результати. Суть авторського підходу полягає в ствердженні того, що мет… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Sports activities can be also recommended as supplementary to the compulsory ones. The soundness of that recommendation has been reconfirmed by the relatively higher level of physical development among student athletes (Salatenko et al, 2015;Pichurin, 2018;Kostyunin, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Sports activities can be also recommended as supplementary to the compulsory ones. The soundness of that recommendation has been reconfirmed by the relatively higher level of physical development among student athletes (Salatenko et al, 2015;Pichurin, 2018;Kostyunin, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…The studies (Оstаpеnkо, 2015) have confirmed that important figures for IT professionals are attentional capacity, sharing and span of attention. The increase in the overall level of physical development of students, and especially the improvement in performance of student's "shuttle run 4 × 9 meters", significantly affects their level of development of attentional selectivity (Pichurin, 2018). Thus, it has been proved once again (Ostapenko, 2014) that dexterity exercises improve the concentration and span of attention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations